Supratimas ir subjektyvumas: hermeneutinės H.G. Gadamerio ir K. O. Apelio strategijos - Borisov, Evgenij (Problemos, 2004)
Polemic of K.-O. Apel against H.-G. Gadamers philosophical hermeneutics moots the question about the difference between ontological and methodological approaches to the phenomenon of understanding. This problem is treated in the paper on the ground of the analysis of the role of subjectivity in the communicative and hermeneutical models of the two thinkers. The results is the contrast between the pragmatic “regulative idea” of the total subjectivity in Apel and the ontological destruction of subjectivity in Gadamer. The author assumes that it can contribute to the demarcation between pragmaticmethodological and ontological strategies in hermeneutics.
Keywords: Hermeneutics; Gadamer; Apel; Subjectivity